Effectiveness of training and management knowledge on employee performance - Sari, Irma; Novi, Novi; Fauziah, Noviani Lulu; Haryadi, Didit (Institute of Computer Science (IOCS), 2024)
In an effective management system, the importance of human resources is increasing. Employee performance is an essential factor influencing success. In an organization, this is one of the most critical functions of a company. This study aims to determine the variables that affect employee performance and develop a theoretical basis and research model. This study used an associative descriptive quantitative method with a population of 50 respondents drawn into samples using non-probability sampling using saturated sampling / total sampling methods—data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis states that employee performance is influenced by the effectiveness of training, meaning that the better the effectiveness of training, the more improved the employee's performance. Thus, the second hypothesis states that employee performance is influenced by knowledge management, meaning that the higher the knowledge management possessed by employees, the higher the performance of employees. The third hypothesis is that employee performance is influenced by the effectiveness of training and management knowledge that can simultaneously improve employee performance. This research is expected to provide theoretical contributions to the literature in this context, certainly in the context of human resource management.